Integrating gender and social inclusion in WP2 Workplan - Kawarazuka, Nozomi (International Potato Center, 2022)
The presentation tackled how to integrate gender and social inclusion in the CGIAR Initiative on Asian Mega-Delta’s (AMD) Work Package 2: Nutrition Sensitive Deltaic Agri-food Systems. Workplan. It was presented during the AMD Work Package 2 - Nutrition Sensitive Deltaic Agri-food Systems Planning Workshop in Penang, Malaysia on 17 October 2022.